Perception Towards COVID-19 Related Symptoms and Traditional Medicine Used for Their Management Among Patients and Their Attendants in Ethiopian Comprehensive Specialized Hospitals: A Cross-Sectional Study - Tegegne AA; Mulugeta A; Genetu B; Endale A; Elias A (Infection and Drug Resistance, 2022)
Addisu Afrassa Tegegne,1 Abel Mulugeta,2 Betelhem Genetu,2 Abyot Endale,3 Asrat Elias1 1Department of Pharmaceutical Chemistry, School of Pharmacy, University of Gondar, Gondar, Amhara Region, Ethiopia; 2Department of Clinical Pharmacy, School of Pharmacy, University of Gondar, Gondar, Amhara Region, Ethiopia; 3Department of Pharmacognosy, School of Pharmacy, University of Gondar, Gondar, Amhara Region, EthiopiaCorrespondence: Addisu Afrassa Tegegne, Email addisu.afrassa@uog.edu.etBackground: Since the beginning of the pandemic, scientists and researchers are highly engaged in the discovery and production of vaccines and specific treatments for COVID-19. In China, the National Health Commission has declared the use of herbal medicine combined with Western medicine as a treatment for COVID-19 and has issued many guidelines on herbal medicine-related therapies. Ethiopians have a variety of medicinal herbs to treat various viral diseases. Hence, this study aimed to assess the perception of the respondent towards COVID-19 related symptoms and traditional medicine practice for their management.Methods: A hospital-based cross-sectional study was done among 423 patients and patient attendants at the University of Gondar Comprehensive Specialized Hospital from August 6 to 27, 2021. Data were collected using a structured questionnaire, and the data were entered into Epi Info 7 and then analyzed with SPSS 20. The association between the independent and dependent variables was explained using chi-square test.Results: A total of 423 respondents participated in the study; 414 (97.9%) participants heard about COVID-19 and responded correctly to the chief clinical symptoms. Fever is the most perceived symptom, reported by 378 (91.3) respondents, and the least reported symptom was loss of taste and smell by 30 (7.2%) respondents. This study showed that home remedies were practiced by 323 of the total respondents, and herbal medicines were the second most and practiced by 316 respondents. Monthly income and perceived knowledge about chief symptoms were statistically significantly associated (p < 0.05) with the use of complementary and alternative medicine for the management of COVID-19 related symptoms.Conclusion: This study found that most of the respondents have knowledge about the signs and symptoms of COVID-19 and the traditional medicine is being practiced by most of the study participants as a management for COVID-19 and related symptoms.Keywords: COVID-19, complementary and alternative medicine, Ethiopia